2019
DOI: 10.1021/acs.jpcc.9b05036
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Objective NSGA-II-Based Optimization Program and Its Application in Reactive Force Field for 2,4,6-Trinitrotoluene Diffusion in the Aqueous Phase

Abstract: The reactive force field (ReaxFF) molecular dynamics simulation is an effective method to study the behavior of energetic materials in the aqueous phase. In order to optimize the ReaxFF of energetic materials in the aqueous phase, we have developed a multiple objective nondominated sorting genetic algorithm II (NSGA-II)-based optimization program (MONOP). The MONOP was used by adopting the CHON-2017_weak as the initial force field to re-optimize the force field of a 2,4,6trinitrotoluene (TNT)/water system. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…], and nitroamine compounds [RDX, 1,3,5,7-tetranitro-1,3,5,7-tetrazolidine (HMX), hexanitrohexaazaisowurtzitane (CL-20), etc.]. For the aromatic energetic materials represented by TNT, the π bond of the benzene ring has a strong attraction to hydroxide anions, so bimolecular substitution reactions tend to occur in such materials and then generate nitrite anions. ,, The heat of such reactions is approximately 3 times the energy barrier. For the nitrate ester compounds represented by NC, experiments have shown that the alkaline hydrolysis reactions do not open rings until all nitrogen-containing groups are eliminated and simultaneously produce nitrate anions and nitrite anions. ,,, There is a great challenge of transition state (TS) analysis to clearly elucidate these reaction results. ,, For the nitramine compounds represented by RDX, the process of producing nitrite anions and the process of proton transfer belong to the same TS .…”
Section: Introductionmentioning
confidence: 99%
“…], and nitroamine compounds [RDX, 1,3,5,7-tetranitro-1,3,5,7-tetrazolidine (HMX), hexanitrohexaazaisowurtzitane (CL-20), etc.]. For the aromatic energetic materials represented by TNT, the π bond of the benzene ring has a strong attraction to hydroxide anions, so bimolecular substitution reactions tend to occur in such materials and then generate nitrite anions. ,, The heat of such reactions is approximately 3 times the energy barrier. For the nitrate ester compounds represented by NC, experiments have shown that the alkaline hydrolysis reactions do not open rings until all nitrogen-containing groups are eliminated and simultaneously produce nitrate anions and nitrite anions. ,,, There is a great challenge of transition state (TS) analysis to clearly elucidate these reaction results. ,, For the nitramine compounds represented by RDX, the process of producing nitrite anions and the process of proton transfer belong to the same TS .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, genetic algorithms have been widely used in the optimization design of internal combustion engines. Among them, (Non-dominated Sorting Genetic Algorithm (NSGA)-II has obvious advantages in convergence speed and optimization results [6]. Jin et al [7] optimized the NSGA-II so that the gasoline/diesel RCCI can cover a larger operating load with higher fuel economy and lower exhaust emissions, but the engine is sensitive to initial conditions and boundary conditions, and corresponding measures need to be taken to guarantee the stability of its operation.…”
Section: Introductionmentioning
confidence: 99%